Thermal evaluation of a component heating system for a monastery cell with measurements and CFD simulations. (July 2021) - Brandl, D.; Mach, T.; Heimrath, R.; Edtmayer, H.; Hochenauer, C.
Abstract: This paper presents a comprehensive analysis of the thermal behaviour and the flow characteristics of a monastery cell with integrated component heating system (CHS). For the evaluation of the system the heating characteristics and the resulting thermal behaviour was investigated. The intention was to develop a model for similar thermal refurbishment projects using wall-integrated low-temperature component heating systems. In a first step a long-term measurement campaign was installed in the monastery cell to gather real life data. In a second step a stationary and transient three-dimensional Computational Fluid Dynamics (CFD) simulation was set up, followed by the validation of the CFD simulation model using the collected measurement data. The CFD model included the entire surrounding building structure, the CHS hot water circuit and the inner air space. The here presented study contains a detailed analysis of the heating up and cooling down phase of the CHS and the total cell. The influence of the most important heating parameters like the water supply temperature or the mass flow rate as well as the influence of the solar radiation or different heating pipe plaster materials on the thermal behaviour of the cell air space and building structure was investigated. Furthermore, a parameter analysis was made in which the CHS was compared with a conventional radiator system. Highlights: Thermal behaviour and the flow characteristics of a single monastery cell. Thermal evaluation of an unconventional component heating system. Comparison between measurement data and results from transient 3D-CFD simulations. CFD model contains interior space, surrounding building structure and water flow. CFD Parameter analysis using stationary 3-D CFD simulations.